PERANCANGAN WEBSITE MULTIMEDIA SEBAGAI MEDIA PROMOSI DAN INFORMASI DI CABANG UTAMA CV. GAPA AC MOBIL - Bagas Alivia Muhammad; Ricky Ramadhan Harahap; Nova Mayasari (CV. Hawari, 2026)
The development of information technology encourages business actors to optimize digital media as a means of communication and promotion. The main branch of CV. Gapa AC Mobil currently does not have an integrated official website, so the delivery of service information and workshop activities is still limited. This research aims to develop a multimedia website that is able to become an information center as well as a digital promotional media for the company. The system development method applied is the Systems Development Life Cycle (SDLC) with the Waterfall model which is carried out in stages starting from needs analysis, system design, database design, implementation, testing, to the maintenance stage. The design includes the development of a responsive and structured interface and the design of a database using MySQL managed through phpMyAdmin to support the management of service data, portfolios, and company information. The implementation of the system is carried out using PHP as the main programming language combined with HTML, CSS, and JavaScript to build an interactive display. The test is carried out using the Black Box Testing method to ensure that each feature runs according to the specifications of the needs. The results of the development show that the resulting website is able to present information in a more organized manner, improve ease of access for customers, and support the company's digital promotion strategy. The existence of this website is expected to strengthen the professional image and increase the competitiveness of CV. Gapa AC Mobil in the face of